Analysis Of Motivation, Market Introduction, Innovation, And Entrepreneurial Commitment Towards The Performance Of Tomang Khas Fakfak Craft Micro Business Group - Fitria Azis Dacing; Titis Istiqomah; Suryono Suryono; Nanik Setyaningsih (Research Trend in Technology and Management, 2024)
The research aims to determine the entrepreneurial mental readiness of tomang craftsmen in Gewerpe village towards increasingly open creative economic market competition; in order to foster and accelerate the economic development of Fakfak regency. Descriptive research uses a semi-qualitative approach through the application of weighting techniques and presenting the analysis results in a compilation between the spider diagram method and the gap analysis method. The 73 respondents were tomang craftsmen and community leaders in Gewerpe village, Fakfak district. The research results show that innovation to create tomang products is good, but the products produced have not been able to enter the competitive global creative economy market. Weak business motivation, recognition of the craft market, and commitment to doing business that is acceptable in the global market; is something that still needs to be improved